Investigation of Nutritional Behaviors in the First and Second Trimesters in Pregnant Women Referring to Clinics in Hamadan, Iran, in 2013 - Masoumi, Seyedeh Zahra (Glob J Health Sci, 2016)
BACKGROUND: Pregnancy is a particular period in women’s life that is accompanied by an increase in nutritional needs. Having a normal pregnancy period and successful pregnancy outcomes depends on the intake of sufficient amount of food. The present study aimed to determine nutritional behaviors in pregnant women in the first and second trimesters referring to clinics in Hamadan, Iran. METHODS: This cross-sectional study was conducted on 170 women referred to health and treatment centers of Hamadan in 2013. Among Hamadan’s health and treatment centers, 10 were selected as the research setting through cluster sampling. Then, the pregnant women at 8-24 weeks of gestation were randomly entered into the study. The data were collected using nutritional behaviors questionnaire in three months. Accordingly, mean scores below 50, between 50 and 75, and above 75 were considered as weak, moderate, and perfect nutritional behaviors, respectively. The data were analyzed using the SPSS statistical software, version 21 and P<0.05 was considered as statistically significant. RESULTS: The results showed that more than three fourths of the study participants had moderate nutritional behaviors. Insufficient intake of fruit, vegetables, and cereals was detected in 80.6%, 54.1%, and 47.1% of the participants, respectively. Besides, 30% of the women had not used folic acid supplement during their pregnancy period or were not aware of its necessity. The results of multivariate analysis indicated that age was only significantly associated with pregnant women’s score of nutritional behaviors (P=0.010). Additionally, no significant relationship was found between the women’s nutritional behaviors and their strategies for elimination of common pregnancy complications, such as constipation, heartburn, urinary tract infection, and anemia. DISCUSSION AND CONCLUSION: Considering the participants’ moderate nutritional behaviors, health and treatment centers are recommended to provide the necessary training for improving pregnant women’s nutritional behaviors and supervise and follow their execution and evaluation.